Penerapan Model Pembelajaran Inkuiri Terbimbing Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa - Yuni Rhamayanti; harahap, mukmin; Lynni Suryani; Sri Rezeki Pakpahan (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2022)
This research is a classroom action research (classroom action research) conducted collaboratively between researchers and mathematics teachers in class VII-2 SMP Negeri 3 Padangsidimpuan for the academic year 2021-2022. The subjects of this study were all seventh grade students. Techniques in collecting data in this study were tests, observation interviews and questionnaires. From the results of the validity of the first cycle student problem solving test instrument above, it was found that all items had a minimum validation correlation of moderate category, so that all items could be used for evaluation in this study. the results of the difficulty level of the problem-solving ability test instrument above, it was found that the percentage interval of the difficulty level of the questions was at 27%-73%, with the minimum item category being moderate. All questions are not too difficult and not too easy, so they can be used for evaluation in this study. The implementation stages of this classroom action research include: Action planning, In this stage a plan will be made in the form of activities that will be carried out by the teacher in planning classroom action research on the application of problem-based learning strategies, Implementation of actions, In this stage, the teacher conveys the competencies to be achieved during the learning process, Observation, In this stage, observations are made of student and teacher activities in the learning process, Reflection. At this stage, classroom action research will continue if the level of problemsolving ability of students in the circle material mathematics lesson is marked by student learning mastery that has not reached 80% in the good category, then improvements are made in the next cycle. This research is planned for two cycles, if in two cycles the teacher feels that the performance indicators that have been formulated previously, then something has not been resolved, then proceed to the next cycle with the stages as has been done in the second cycle of course with improvements. The first and second cycles consisted of 3 meetings. Student activity increases with the use of the guided inquiry learning model. This can be seen from the results of the observation of student activities in the first cycle, 79.58% are still in the